2020
DOI: 10.1177/1550059420918755
|View full text |Cite
|
Sign up to set email alerts
|

Habituation of P300 in the Use of P300-based Brain-Computer Interface Spellers: Individuals With Amyotrophic Lateral Sclerosis Versus Age-Matched Controls

Abstract: The P300-based brain-computer interface speller can provide motor independent communication to individuals with amyotrophic lateral sclerosis (ALS), a progressive neurodegenerative disorder that affects the motor system. P300 amplitude stability is critical for operation of the P300 speller. The P300 has good long-term stability, but to our knowledge, short-term habituation in the P300 speller has not been studied. In the current study, 15 participants: 8 ALS patients and 7 age-matched healthy volunteers (HVs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Apart from the task differences, age was considered as a confounding factor in BCI studies. 26 Yu et al 27 applied P300 BCI and compared the detailed EEG signal characteristics in several selected channels between age-matched subjects. In our study, we used partial correlation and took age as a covariate.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the task differences, age was considered as a confounding factor in BCI studies. 26 Yu et al 27 applied P300 BCI and compared the detailed EEG signal characteristics in several selected channels between age-matched subjects. In our study, we used partial correlation and took age as a covariate.…”
Section: Discussionmentioning
confidence: 99%
“…Another implication that we may derive from the influence of CR on EEG reported in the reviewed studies concerns the potential benefits for the development of brain–computer interface (BCI) systems. Such systems refer to devices that operate based on brain signals rather than motor movements, providing an alternative communication channel (Velasco-Álvarez et al, 2013; Yu et al, 2021). For example, some studies reported that people with a neurodegenerative disease or old age may face difficulties when interacting with BCI systems because brain wave patterns may be less differentiable (Belkacem et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As for the habituation phenomenon, Yu et al [35] recently investigated the short-term habituation in the use of P300-based spellers and concluded that neither intra-run nor inter-run P300 habituation was found.…”
Section: Human Factors In P300 Detectionmentioning
confidence: 99%
“…In [49], researchers conducted a comparative study concluding that BCI accuracy and communication rate did not significantly differ between users with ALS and healthy, age-matched volunteers. Recently, Yu et al [35] conducted a comparative study involving people with ALS and healthy age-matched volunteers to study the habituation in the use of P300based spellers. Results showed that the ALS group performed as well as the healthy volunteers, concluding that P300 speller can be a reliable communication device for individuals with ALS.…”
Section: Characteristics Of the Participantsmentioning
confidence: 99%